Assessment of the impact of renewable energy and energy efficiency policies on the Macedonian energy sector development - Dedinec Kanevche, Aleksandra; Taseska-Gjorgievska, V; Markovska, Natasa; Kanevce, G; Goldstein, G; Pye, S (American Institute of Physics, 2013)
The main goal of this paper is to examine and quantify how the development of the energy system in Macedonia could be influenced by policies and programs that promote energy efficiency and renewable energy, in terms of energy security and diversification, economic competitiveness, and CO2 mitigation. For this purpose, the MARKAL-Macedonia national energy planning model was used. These policies are explored by comparing a reference (business-as-usual) development of energy system with three alternative policy scenarios: (1) Renewable Energy (RE) Scenario—introducing a renewable energy target by 2020 in line with that proposed by the Energy Community; (2) Energy Efficiency (EE) Scenario—exploring the range of energy efficiency measures that are the most cost-effective means to meet national targets aimed at reducing final energy consumption; and (3) Combined RE and EE Scenario—a combination of supply-side and demand-side approaches that examine the resulting synergies of these policy goals. For each scenario, the implications of least-cost investment options for new capacity builds, investment spending requirements, electricity prices, fuel expenditures, and carbon dioxide emissions were assessed. The analyses have shown that even under the Reference scenario, the reliance on electricity import will be reduced, as a result of increased gas import. The RE scenario further reduces the overall import by 3% while the EE scenario by 12%. Total discounted costs of the energy system in the Reference scenario is estimated to nearly e36 billion, with investment of e3.773 billion for 2.803 GW of new electricity generation capacity needed to meet the increased demand by 2030. The proposed RE target increases the cost of the energy system only by 0.13%, due to the availability of additional renewables, particularly hydro, biomass, and biofuels. The combination of the policies that promote increased energy efficiency will decrease the discounted energy system costs of 0.24% (e87 million net present value). The baseline evolution of the energy system results in 59% increase of CO2 emissions over the planning horizon. The analyzed RE and EE policies show strong synergies with a move to a lower carbon economy, resulting in cumulative CO2 emissions reduction of 3.7% triggered by an overall drop in consumption and less use of fossil fuels. VC 2013 AIP Publishing LLC. [http://dx.doi.org/10.1063/1.4813401]